2023
DOI: 10.1038/s41398-023-02414-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of psychedelic drug exposure on central amygdala reactivity and behavioral responding

Abstract: Psilocybin and its active metabolite psilocin have been shown to elicit rapid and long-lasting symptom improvements in a variety of affective psychiatric illnesses. However, the region-specific alterations underlying these therapeutic effects remain relatively unknown. The central amygdala (CeA) is a primary output region within the extended amygdala that is dysregulated in affective psychiatric disorders. Here, we measured CeA activity using the activity marker c-Fos and CeA reactivity using fiber photometry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 80 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…Although psilocybin induces inhibitory effects in many subcortical regions via 5HT1Rs, direct psychedelic-induced cellular inhibition in cortical neurons was reported for the first time recently 82 . This suppression of Acq-dominant neurons in psilocybin responders echoes recent findings that inhibitory plasticity in fear memory engrams in the hippocampus is necessary for the development memory selectivity, measured by the relative reduction of freezing in neutral contexts over time 83 . Perhaps psilocybin invokes a similar mechanism to accelerate extinction learning.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although psilocybin induces inhibitory effects in many subcortical regions via 5HT1Rs, direct psychedelic-induced cellular inhibition in cortical neurons was reported for the first time recently 82 . This suppression of Acq-dominant neurons in psilocybin responders echoes recent findings that inhibitory plasticity in fear memory engrams in the hippocampus is necessary for the development memory selectivity, measured by the relative reduction of freezing in neutral contexts over time 83 . Perhaps psilocybin invokes a similar mechanism to accelerate extinction learning.…”
Section: Discussionsupporting
confidence: 84%
“…One possibility is that these neurons are salience or valence-sensitive. Notably, a single-dose of psilocin reduces neural activities to aversive airpuffs in the central amygdala days later, hinting that weakened neural activities within negative valence-encoding circuits may partially contribute to this observation 77 . In the RSC, our data and model suggest that Acq- and Ext3- dominant ensembles contain neurons responsive to shock or shock omission, stimuli of opposite valence.…”
Section: Discussionmentioning
confidence: 98%
“…One notable limitation of these studies is the use of male mice only; direct assessment of sex differences in this response are being pursued, given well-established knowledge regarding differential stress responses, , as well as emerging evidence of differential psychedelic responses, in male and female rodents. , Another limitation is that the roles of IP injection-related stress versus drug-related stress in the treated animals were not fully isolated from one another; the use of minimally stressful administration techniques for psilocybin (such as infusion through a pre-implanted IV catheter) could lend further clarity to this dimension in future studies. A final consideration is that a longer period was required to observe long-term effects of drug administration in the OFT, potentially making measurements at this time point more reflective of perseverative exploratory behaviors than of behavioral response to a novel, anxiety-provoking environment.…”
Section: Discussionmentioning
confidence: 99%
“…The key outcomes of this study underline the fact that animal studies are required for understanding the mechanisms that underlie the therapeutic efficacy of psilocybin because they allow detailed interrogation of behaviour and brain function in the absence of effects of expectancy. It is important to note that female animals were used exclusively in these studies and that psilocybin has been shown to have effects that differ based on biological sex in rats and mice in terms of behaviour 95 , regional brain reactivity 96 and structural neuroplasticity 46 . Future studies should aim to examine how psilocybin influences serotoninergic tone via other (i.e.…”
Section: Discussionmentioning
confidence: 99%